Apelin System in Mammary Gland of Sheep Reared in Semi-Natural Pastures of the Central Apennines - Mercati, Francesca (Animals (Basel), 2018)
SIMPLE SUMMARY: Grazing activity is fundamental to natural grassland biodiversity preservation. Increasing summer aridity decreases the grassland pastoral value, negatively affecting animal morpho-functional features and production with detrimental effects on the extensive sheep farming sustainability. Since adipokines represent a link between a subject’s energy availability and tissue metabolism, we investigated the presence and distribution of the system composed of the adipokine apelin and its receptor in the mammary gland of sheep during the period between maximum flowering and maximum dryness of the pasture, providing a group of sheep with food supplementation. This work represents a part of a wider study aimed to buffer the negative effects of increasing summer drought stress on farm income and to maintain the grassland biodiversity. Our findings improve the knowledge of apelin/receptor system function on the sheep mammary gland and this could be a useful tool in the farm management practices. ABSTRACT: Sheep are the most bred species in the Central Italy Apennine using the natural pastures as a trophic resource and grazing activity is fundamental to maintain the grassland biodiversity: this goal can be reached only ensuring an economical sustainability to the farmers. This study aimed to investigate the apelin/apelin receptor system in ovine mammary gland and to evaluate the differences induced by food supplementation, in order to shed light on this system function. A flock of 15 Comisana x Appenninica adult dry ewes were free to graze from June until pasture maximum flowering (MxF). From this period to pasture maximum dryness (MxD), in addition to grazing, the experimental group (Exp) was supplemented with 600 g/day/head of cereals. Apelin and apelin receptor were assessed by Real-Time PCR and immunohistochemistry on the mammary glands of subjects pertaining to MxF, MxD and Exp groups. They were detected in alveolar and ductal epithelial cells. The pasture maximum flowering group showed significant differences in apelin expression compared with experimental and MxD groups. Apelin receptor expression significantly differed among the three groups. The reduced apelin receptor expression and immunoreactivity levels during parenchyma involution enables us to hypothesize that apelin receptor plays a modulating role in the system control.